1982
DOI: 10.1002/eji.1830120611
|View full text |Cite
|
Sign up to set email alerts
|

IgM‐ and IgD‐bearing peripheral blood lymphocytes differentiate to IgM but not IgG or IgA immunoglobulin‐secreting cells

Abstract: Human peripheral blood mononuclear cells were depleted of surface IgM+ or IgD+ cells and assayed for mitogen-induced differentiation to immunoglobulin-secreting cells (ISC) of IgM, IgG and IgA classes. Stimulatory agents included T cell-dependent pokeweed mitogen, B cell mitogen Staphylococcus aureus bacteria strain Cowan I, and a combination of the two which gives uniform, high levels of ISC from all normal donors. Depletion of either IgM- or IgD-bearing B lymphocytes resulted in loss of cells bearing the oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1986
1986
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…As non-Ig controls, we routinely analyzed HLA-A,B antigens to afford a diagnosis of N-linked glycan type in cultures where Ig synthesis was strongly inhibited. It should be emphasized that addition of inhibitor is required at a timepoint preceding significant Ig synthesis, which is on day 3 or later, in PWM -SAC stimulated cultures (Saiki and Ralph, 1981;Scholten et al, 1986). We conclude that in the presence of SW, terminal modifications can take place, resulting in the addition of a single sialic acid per N-linked glycan and acquisition of EndoH resistance.…”
Section: Stimulation Of Human Mononuclear Cells (Mnc)mentioning
confidence: 80%
See 1 more Smart Citation
“…As non-Ig controls, we routinely analyzed HLA-A,B antigens to afford a diagnosis of N-linked glycan type in cultures where Ig synthesis was strongly inhibited. It should be emphasized that addition of inhibitor is required at a timepoint preceding significant Ig synthesis, which is on day 3 or later, in PWM -SAC stimulated cultures (Saiki and Ralph, 1981;Scholten et al, 1986). We conclude that in the presence of SW, terminal modifications can take place, resulting in the addition of a single sialic acid per N-linked glycan and acquisition of EndoH resistance.…”
Section: Stimulation Of Human Mononuclear Cells (Mnc)mentioning
confidence: 80%
“…The synergy between PWM and SAC has been interpreted as evidence in favour of a two-signal model for B cell activation (Saiki and Ralph, 1981;Falkoff et al, 1982). For most donors, the combination of PWM and SAC acts synergistically.…”
Section: Stimulation Of Human Mononuclear Cells (Mnc)mentioning
confidence: 99%
“…Analysis of B‐cell division by flow cytometry and carboxy‐fluorescein diacetate, succinimidyl ester (CFSE) labelling has shown that five days of in‐vitro stimulation is long enough for the cells to undergo at least four division cycles and that this number of division cycles is necessary for antibody secretion 19 . This system preferentially activates memory B cells, 26,27 and induces IgM memory B cells (CD27 + IgM + IgD + ) to secrete IgM and IgG, while class switched memory B cells (CD27 + IgM – IgD – ) will secrete IgG and IgA 28 . The SAC + IL‐2 system probably induces a mixture of pre‐existing memory B cells and newly generated precursor plasma cells to secrete antibody.…”
Section: Discussionmentioning
confidence: 99%
“…They, however, failed also to produce significant levels of IgG, confirming the previous finding that SAC plus IL-2 is not sufficient to induce class switch in vitro. 15 The data presented in Table 2 also explain why in cultures of PBLs stimulated with SAC plus IL-2 it is impossible to correlate IgM production in vitro to the IgM memory B-cell pool: In the presence of CD4 ϩ T cells, both CD27 Ϫ IgM ϩ naive B cells and CD27 ϩ IgM ϩ memory B cells are induced to IgM production.…”
Section: Isolated Naive B Cells Of Healthy Donors Do Not Produce Igm mentioning
confidence: 99%